20 Comparison of native myocardial T1 and T2 mapping at 1.5T and 3T in healthy volunteers following installation of new scanners. (28th January 2023) - Tsoumani, Zoi; Nakou, Eleni; Alpendurada, Francisco; Pennell, Dudley J; Lota, Amrit
Abstract : Introduction: Cardiovascular magnetic resonance (CMR) parametric mapping is a robust technique to quantify myocardial pathology such as oedema. We sought to evaluate the extent of any sequence or scanner specific changes in T1 and T2 mapping times from previously established local normal ranges following the installation of 3 new CMR scanners in the new Diagnostic Centre at Royal Brompton Hospital. Materials and Methods: Healthy volunteers were scanned in the new 1.5T and 3T Siemens scanners. All subjects underwent T1 mapping using modified Look-Locker inversion recovery MOLLI sequence (using scheme 5s(3s)3s) and T2 mapping as T2-prepared single-shot bSSFP sequence. Segmental and global myocardial values were acquired from short-axis views with 10% endocardial and epicardial offsets using CVI42. Data was analysed in SPSS. Results: Twenty-four volunteers were scanned at 1.5T (female/male 15/9, age 46.2 ± 14 years) and sixteen at 3T (female/male 6/10, age 38 ± 12 years). There was no significant difference between the new and old T1 values at 1.5T (T1global 1022 ± 20 msec vs 1015 ± 25msec, p=0.430, T1mid septal 1017 ± 29 msec vs 1011 ± 29 msec, p=0.619) and 3T (T1global 1249 ± 21 msec vs 1260 ± 30 msec, p = 0.094, T1mid septal 1265 ± 29 msec vs 1275 ± 29 msec, p =0.191). Similarly, there was agreement between the new and old T2 values in 1.5T (T2global 48.2 ± 2.3 msec, p = 0.109 and T2mid septal 48.3 ± 2.2 msec vs 47.3 ± 3.2 msec, p = 0.337) and 3T (T2global 40.0 ± 2.4 msec vs 39 ± 2 msec, p = 0.864 and T2mid septal 42.3 ± 3.8 msec vs 41 ± 2 msec, p = 0.447). Conclusion: This study confirms that T1 and T2 mapping times were not significantly different following recent scanner upgrades within the same institution both through segmental and global analyses. The collection of data on local standard deviation has also facilitated the introduction of Z-scores to clinical reports to aid interpretation of mapping data across multiple field strengths. References: Kranzusch R, Aus dem Siepen F, Wiesemann S, Zange L, Jeuthe S, Ferreira da Silva T, et al . Z-score mapping for standardized analysis and reporting of cardiovascular magnetic resonance modified Look-Locker inversion recovery (MOLLI) T1 data: Normal behavior and validation in patients with amyloidosis. J Cardiovasc Magn Reson 2020;22 (1):6. Messroghli DR, Moon JC, Ferreira VM, Grosse-Wortmann L, He T, Kellman P, et al . doi: 10.1186/s12968–017–0389–8. Clinical recommendations for cardiovascular magnetic resonance mapping of T1, T2, T2* and extracellular volume: A consensus statement by the Society for Cardiovascular Magnetic Resonance (SCMR) endorsed by the European Association for Cardiovascular Imaging (EACVI). J Cardiovasc Magn Reson . 2017 Oct 9;19:75.